Dietary quality and nutrient intakes of elite paracyclists - Shaw, K. A.; Chilibeck, P. D.; Warkentin, T. D.; Zello, G. A. (Nutrients, 2024)
Nutrient requirements for para-athletes will be influenced by a variety of factors secondary to their impairment and, therefore, recommendations for para-athletes cannot be drawn directly from that of able-bodied athletes. Information on the dietary intakes of para-athletes is lacking and therefore needs to be examined. This study assessed the nutrient intakes and diet quality of 31 paracyclists via food frequency questionnaires. Based on the dietary reference intakes, most paracyclists consumed intakes above the recommended dietary allowance (RDA) or adequate intake (AI). Recommendations were not met for iodine (males = 87% RDA; females = 62% RDA) or fibre in males (84% AI). A 26% risk of inadequacy was noted for vitamins D and E in females. A total of 42% of females and 75% of males did not meet fibre recommendations (14 g/1000 kcal), and only three athletes (all females) consumed fatty acids in the recommended omega-6 to omega-3 ratio of 4:1 or less. Athletes consumed grains, fruits, and vegetables frequently, though whole grains, pulses, and oily fish were generally consumed less often. Paracyclists appear to be consuming intakes at or above recommendations for most nutrients, though several nutrients were consumed below the recommended amounts; therefore, increasing the variety of foods consumed is suggested.